The prevalence of atopic dermatitis among children aged between 6 months and 12 years attending primary health care clinics in Qatar 2018-2019 - Oommen, Boby John; Kadori, Waad Ibrahim Majeed; Abdulmajeed, Jazeel; Krishnan, Jeyaram Illiayaraja; Veettil, Shajitha Thekke (International Journal of Research in Medical Sciences, 2022)
Background: The prevalence of atopic dermatitis among children appears to have increased dramatically over the past decades. Such rapid increase in prevalence cannot be explained fully. Genetic factors, microbiomes (especially staphylococcus aureus infection), food allergy and environmental factors might play a role in such an increment. This study aimed to report the prevalence of atopic dermatitis among children aged 6 months to 12 years attending primary health care centers in Qatar during the year 2018 and 2019. Methods: Cross-sectional retrospective data analysis of all registered cases having at least one visit in any of the 28 health centers dermatology clinics operated by PHCC with a verified diagnosis of atopic dermatitis Results: Out of 4521 patients dermatology clinic visit, 1359 had atopic dermatitis during the period of 2018 and 2019, and the prevalence rate is 30.06 (95% CI 28.72-31.42). In this 1359 atopic dermatitis cases, mean age of patients was 5.09±3.53 years and ranged from 6 months to 12 years. In this 18.9% was <1 years, 41.43% was 1-5 years, 19.35% was 5-8 years and 21.04% was 8-12 years. Prevalence of AD is high in boys 31.42% than girls 28.81% and is high in Qatari population 34.4% than the non-Qatari population 28.7%. The most frequently prescribed medication group was topical emollients (89.8%) followed by antihistamine (81.24%) and antibiotics (56.73%). Steroids were prescribed only for 7.3% of cases. Conclusions: In this study the prevalence of atopic dermatitis was remarkably very high in young children in Qatar. Further prospective research and more efforts are needed to develop a standard treatment regimen for allergic diseases in Qatar.